WIARA I ROZUM: JAKA RELACJA? - Possenti, Vittorio (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article shows that the relationship between faith and reason has been intrinsic to Christianity since its beginnings and runs through the history of theology, of the Church and Christian thought. There are various ways in which the main theme can be introduced: one of them is to consult the foremost theologians and Christian thinkers who have thought and written on this subject. In this paper it appears more opportune to refer to two documents: the Encyclical Faith and Reason (FR, 1998) of St.Pope John Paul II, and the speech given at the University of Regensburg by Benedict XVI (2006). The different aim of the carefully worked out encyclical letter (it is more than one hundred pages long), addressed to the Catholic Bishops by St. John Paul II, and the brief academic speech given by Pope Benedict XVI makes their basic convergence all the more significant. Furthermore, the Regensburg speech is less easily understood without the foundation laid by the encyclical FR.